MAXIMIZING FARMER EARNINGS THROUGH THE INTEGRATION OF AGRO-FORESTRY MODELS AND SMALL RUMINANT PRODUCTION - N. , Arulnathan; M. , Chellapandian; D. , Thirumeigananam (International Journal of Allied Sciences (IJAS), 2022)
A recent study investigated the potential of doubling farmers' income by integrating various agro-forestry models with small ruminant production. Three agro-forestry model types were established: Silvipature (Type I), Hortipasture (Type II), and Hortisilvipasture (Type III), each covering an acre of land in the farmers' fields. The study analyzed the economics of these models under irrigated conditions, including establishment costs, expected income from small ruminant integration, and additional income from horticultural plants. Results indicated that the optimal utilization of available land through horti-pasture and horti-silvi-pasture, combined with sheep production, provided additional income for farmers.